Вимоги до об'єкта зобов'язальних правовідносин - Голубєва, Неллі Юріївна; Голубева, Нелли Юрьевна; Golubeva, Nelli (My University, 2013)
The article investigates the basic requirements to the object of obligations (actions of the debtor) for existing of obligations. It is concluded that the object of the obligation must have the following properties: 1) be legally and practically possible (feasible), 2) have value to the creditor, and 3) be sufficiently certain . It was dentified the aspects of the issues.
Голубєва Н. Ю. Вимоги до об'єкта зобов'язальних правовідносин / Н. Ю. Голубєва // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 363-374.
Keywords: зобов'язання; об'єкт зобов'язання; визначеність об'єкту зобов'язання; здійсненність об'єкту зобов'язання; неможливість виконання зобов'язання; виникнення зобов'язання; обязательство; объект обязательства; определенность объекта обязательства; осуществимость объекта обязательства; невозмодность выполнения обязательства; возникновение обязательства; obligation; object of obligation; certainty of object of obligation; feasibility of object of obligations; inability to perform the obligations; occurrence of obligations